PENGARUH KOMITE AUDIT DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA - Diah Nurdiana (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
This study aims to determine: 1) The Effect of the Audit Committee on Earnings Management, 2) The Effect of Company Size on Earnings Management, 3) The Effect of the Audit Committee and Company Size on Earnings Management in Consumer Goods Companies listed on the IDX for the period 2012-2016. The company sample was taken by purposive sampling method where the sample was taken as many as 8 companies from 33 consumer goods companies listed on the IDX for the period 2012-2016. This analysis method used in this research is regression analysis and classical assumption test. Hypothesis testing is done by using t test and f test. The results of this study indicate that partially, the audit committee variable has no significant effect on earnings management, while the company size variable has no significant effect on earnings management. Simultaneously, the Audit Committee and Company Size have no effect on earnings management.